Gaumont Treasures: Jacques Feyder and the Early Masters of French Cinema - Feyder, Jacques; Bosetti, Roméo; Lacroix, Georges-André; Arnaud, Étienne; LeSomptier, René; Fescourt, Henri; Ravel, Gaston (Kino International, 2011)
Jacques Feyder enjoyed a long, fruitful career as director, celebrated for such films as "The Kiss" (1929, starring Greta Garbo) and "Knight Without Armor" (1937, with Marlene Dietrich). Feyder cultivated his talents in the 1910s at the Gaumont Studios, where a carefully-curated stable of innovative directors were advancing the artistic finesse of the adolescent art form. In addition to Feyder’s sophisticated comedies, this volume showcases a wide variety of other forms, impeccably executed: slapstick (The Long Arm of the Law), realism (The Barges), and experimental film (Feet and Hands). This disc also presents samples of the astounding technical achievements that Gaumont had mastered, years before they became standard practice, such as the Phonoscéne, a synchronized sound process presented to the public via the Chronomégaphone sound-on-disc system. [Cover]
Keywords: DVD-Video